Grief and Grievance : Art and Mourning in America - Enwezor, Okwui (New York : Phaidon Press Limited, 2020)
Adkins, Terry ; Basquiat, Jean-Michel ; Beasley, Kevin ; Bey, Dawoud ; Bradford, Mark ; Bradley, Garrett ; Edwards, Melvin ; Frazier, LaToya Ruby ; Gaines, Charles ; Gallagher, Ellen ; Gates, Theaster ; Jafa, Arthur ; LaRue Johnson, Daniel ; Johnson, Rashid ; Jones, Jennie C. ; Joseph, Kahlil ; Lawson, Deana ; Leigh, Simone ; Ligon, Glenn ; Marshall, Kerry James ; Nekkia McClodden, Tiona ; Mehretu, Julie ; Okpokwasili, Okwui ; Pendleton, Adam ; Phillips, Julia ; Pindell, Howardena ; Rowland, Cameron ; Simpson, Lorna ; Smith, Sable Elyse ; Sorey, Tyshawn ; Stingily, Diamond ; Taylor, Henry ; Willis Thomas, Hank ; Walker, Kara ; Ward, Nari ; Weems, Carrie Mae ; Whitten, Jack
Featuring works by more than 30 artists and writings by leading scholars and art historians, this book — and its accompanying exhibition, both conceived by the late, legendary curator Okwui Enwezor — gives voice to artists addressing concepts of mourning, commemoration, and loss and considers their engagement with the social movements, from Civil Rights to Black Lives Matter, that black grief has galvanized. From February 17 to June 6, 2021, the New Museum will present “Grief and Grievance: Art and Mourning in America,” an exhibition originally conceived by Okwui Enwezor (1963-2019) for the New Museum, and presented with curatorial support from advisors Naomi Beckwith, Massimiliano Gioni, Glenn Ligon, and Mark Nash. “Grief and Grievance” will be an intergenerational exhibition, bringing together thirty-seven artists working in a variety of mediums who have addressed the concept of mourning, commemoration, and loss as a direct response to the national emergency of racist violence experienced by Black communities across America. The exhibition will further consider the intertwined phenomena of Black grief and a politically orchestrated white grievance, as each structures and defines contemporary American social and political life. “Grief and Grievance” will comprise works encompassing video, painting, sculpture, installation, photography, sound, and performance made in the last decade, along with several key historical works and a series of new commissions created in response to the concept of the exhibition. (provided by publisher)
Grief and Grievance: Art and Mourning in America, Okwui Enwezor, New Museum, 17.02.-06.06.2021
boek